Influence of biochar on the sorption and leaching of thiamethoxan in soil - Peres, Fernanda Salles Cunha; Petter, Fabiano André; Sinhorin, Adilson Paulo; de Lima, Larissa Borges; Tavanti, Tauan Rimoldi [UNESP]; da Silva Freddi, Onã; Marimon Junior, Ben Hur (Taylor & Francis, 2022)
This study evaluated the long-term effect of biochar application on the sorption and desorption of thiamethoxam in a Haplic Plinthosol. The experiment was conducted in a randomized block design with combination of doses of mineral fertilizer NPK (0 and 300 kg·ha−1 formula 05-25-15) and biochar (0, 16 and 32 Mg ha−1). Deformed soil samples were collected in the field from the 0-0.10 m layer of all plots to determine the sorption and desorption of the thiamethoxam insecticide in the soil; fulvic acid (FA), humic acid (AH) and humin (HUM) carbon contents; and total organic carbon. The Batch slurry method was used to evaluate sorption and desorption. The Freundlich isotherm adequately described thiamethoxam sorption in all treatments. The application of biochar increased the sorption (Kfs) and decreased the desorption (Kfd) of thiamethoxam. The sorption intensity (1/n) showed reduction characteristics as the soil concentration of thiamethoxam increased. Biochar has a sorption effect on the soil through covalent bonds and H-bonds with the insecticide molecules, thereby indirectly increasing the sorption potential in the chemical fractions of the organic matter of soil. The application of 32 Mg ha−1 of biochar significantly reduced thiamethoxam in the soil solution. Altogether, the present study reveals that biochar application in soil is a promising tool for mitigating the contaminant potential of thiamethoxam in subsurface waters.
Keywords: insecticide; Leaching; pyrogenic carbon; soil organic matter; sorption